51 Adherence to cardiologist recommendations regarding extended duration of ticagrelor for patients undergoing PCI for myocardial infarction. (17th July 2020) - Ow, Kok Weng; Parker, William; Onwordi, Eunice; Storey, Robert F
Abstract : Introduction: Ticagrelor is a potent, reversible, platelet P2Y12 receptor antagonist. Patients with a history of a myocardial infarction (MI) have a persistently increased risk for future ischaemic events. PEGASUS-TIMI 54 demonstrated that patients with a history of MI, coupled with a high risk of ischaemic events and absence of conditions associated with excessive bleeding risk, may benefit from extended duration of dual antiplatelet therapy (DAPT) with aspirin 75-150mg once daily and ticagrelor 60mg twice daily (BD) beyond the first year after MI. This strategy is endorsed by current European Society of Cardiology guidelines and approved by NICE. Cardiologists may recommend this strategy but it remains unclear how often this is followed in a primary care setting. Methods: A list of consecutive patients who underwent percutaneous coronary intervention (PCI) between March 2015 to August 2018, performed by a single clinician was obtained. The discharge summaries of these patients were evaluated to determine whether they had been treated for MI and received the recommendation of extended DAPT duration with ticagrelor 60mg BD. The summary care records of patients who were found to have received the recommendation of extended DAPT duration were interrogated to determine compliance with the recommendation. Reasons for non-adherence were recorded if available. Results: 399 patients underwent PCI during the study period. 323 patients (81%) underwent PCI as part of their management for an acute coronary syndrome (ACS) while 76 patients (19%) underwent PCI as an elective case. Of 323 ACS patients, 6 patients died during their ACS hospital admission and were excluded. 61 out of 317 ACS patients (19%) and 3 out of 76 (4%) elective patients were recommended extended duration of ticagrelor with down-titration from 90mg BD to 60mg BD after the first year of treatment. On interrogation of the summary care record more than 1 year after hospital discharge, adherence to the recommendations was observed in 38 out of 61 ACS patients (62%) and 3 elective patients (100%). 23 out of 61 ACS patients (38%) did not receive the recommended lower dose of 60mg BD: 1 patient remained on ticagrelor 90mg BD and required reminder to down titrate; 1 patient was admitted for another ACS and restarted 1 year of ticagrelor 90mg BD; 2 patients discontinued ticagrelor due to rash or breathlessness; and 2 patients received an alternative P2Y12 inhibitor (1 prasugrel, 1 clopidogrel). The remaining 17 patients (28% of patients with recommendation for extended therapy) had no documentation why ticagrelor 60mg BD was not continued. Conclusions: Treatment recommendations for extended DAPT in a discharge letter leads to reasonable levels of adherence but further work is required to determine if improved long-term communication between cardiologists and primary care physicians leads to better care and clinical outcomes following myocardial infarction. Conflict of Interest: None